2009
DOI: 10.1021/ja901308v
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature 65Cu NMR Spectroscopy of the Cu+ Site in Azurin

Abstract: Abstract65 Cu central-transition NMR spectroscopy of the blue copper protein azurin in the reduced Cu(I) state, conducted at 18.8 Tesla and 10 K, gave a strongly second order quadrupole perturbed spectrum, which yielded a 65 Cu quadrupole coupling constant of ±71.2 ± 1 MHz, corresponding to an electric field gradient of ±1.49 atomic units at the copper site, and an asymmetry parameter of approximately 0.2. Quantum chemical calculations employing second order Møller-Plesset perturbation theory and large basis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…1 Blue copper azurins have been extensively characterized by means of multiple techniques which include X-ray diffraction, 3,4 electron paramagnetic resonance 5,6 or nuclear magnetic resonance. 7,8 The pioneering work of E. I. Solomon's group was particularly successful in unveiling the electronic structure of Cu sites in various copper proteins by using a combination of spectroscopic techniques and quantum calculations. [9][10][11][12][13][14] Initially, these seminal works mostly aimed at understanding the main spectroscopic features, especially the investigation of the excited d-states, which are responsible for the peculiar absorption spectra of copper proteins, giving rise, in most cases, to their characteristic intense blue coloration.…”
Section: Introductionmentioning
confidence: 99%
“…1 Blue copper azurins have been extensively characterized by means of multiple techniques which include X-ray diffraction, 3,4 electron paramagnetic resonance 5,6 or nuclear magnetic resonance. 7,8 The pioneering work of E. I. Solomon's group was particularly successful in unveiling the electronic structure of Cu sites in various copper proteins by using a combination of spectroscopic techniques and quantum calculations. [9][10][11][12][13][14] Initially, these seminal works mostly aimed at understanding the main spectroscopic features, especially the investigation of the excited d-states, which are responsible for the peculiar absorption spectra of copper proteins, giving rise, in most cases, to their characteristic intense blue coloration.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard Ellis and Lipton have shown that it is possible to apply CP/CPMG pulse sequences to acquire spectra of quadrupolar nuclei contained in metalloproteins which are dissolved in frozen solutions doped with paramagnetic metal ions (that act to enhance 1 H longitudinal relaxation rates). [52][53][54][55][56] Kervern et al have also demonstrated that the CPMG pulse sequence can be utilized to extend 1 H coherence lifetimes of paramagnetic solids under ultra fast MAS. 57 These findings suggest that T 2 0 may remain long enough such that CPMG experiments remain feasible on systems doped with radicals.…”
Section: Introductionmentioning
confidence: 99%
“…15−19 The moderate Q values for 63 Cu and 65 Cu usually result in nuclear quadrupolar coupling constants C Q on the order of megahertz and thus in broad 63/65 Cu NMR powder line shapes for the central transition (i.e., m S = +1/2 ↔ m S = −1/2) that are challenging to acquire experimentally. 15 Early investigations therefore focused on Cu(I) sites with high symmetry (e.g., tetrahedral) and hence with small quadrupolar interactions. 16 However, in the past decade, high-field NMR magnets have become more widely available, and several wideline solid-state NMR techniques 20−26 have permitted the acquisition of NMR spectra with breadths that sometimes are several megahertz.…”
Section: ■ Introductionmentioning
confidence: 99%